Modelling And Syntheses Of Vanillin Derivatives Targeting Influenza Virus Neuraminidase - Asaruddin, Mohd Razip (2016)
Influenza remains a serious global threat. To date, zanamivir and oseltamivir used as NA inhibitors were reported to be resistant to influenza virus. Therefore, new and effective NA inhibitors must be discovered. In this study, pharmacophore modelling approach was used to search for NA inhibitors with new scaffold. Two computer softwares such as Discovery Studio 2.5 and LigandScout 3.1 was utilized. Through the softwares, the pharmacophore modelling approaches was generated. Ligand-based and structure-based pharmacophore modelling approaches will complement each other. Ligand-based pharmacophore modelling approach is based on common features functional groups.